Online Ambassador Visits for Hospitalized Children With Cancer: Qualitative Evaluation of Implementation - Natasha Nybro Boensvang; Mette Weibel; Claire E Wakefield; Pernille Envold Bidstrup; Marianne Olsen; Karin Bækgaard Nissen; Vibeke Spager; Martin Kaj Fridh; Hanne Bækgaard Larsen (JMIR Publications, 2024)
BackgroundChildren with cancer or cancer-like disease risk treatment-related isolation, which can negatively impact their peer relationships and social competencies and exacerbate their loneliness. During the COVID-19 pandemic, increased online socialization became the new normal imposed by national isolation guidelines. To adhere to the treatment-related isolation guidelines, children with cancer were offered online classmate "ambassador" visits during hospitalization. ObjectiveThis study aimed to identify facilitators and barriers to online classmate "ambassador" visits during children with cancer's hospitalization through a qualitative descriptive process evaluation using the Consolidated Framework for Implementation Research. MethodsFrom January to April 2022, we conducted 39 individual semistructured interviews with hospitalized children (n=16), their classmates (n=16), teachers from their schools (n=3), and study nurses (n=4) from involved hospitals. Most interviews (n=37, 95%) were conducted online using Microsoft Teams or Google Meet, while 2 (5%) interviews were conducted in person at the participants' residences. This approach allowed us to gain a broad understanding of the facilitators and barriers to online ambassador visits. ResultsWe identified four themes: (1) working together, (2) ensuring participation, (3) staying connected, and (4) together online. The themes are described in terms of facilitators and barriers to online ambassador visits with 3 Consolidated Framework for Implementation Research domains: innovation, individuals, and the implementation process. ConclusionsAddressing the social needs of hospitalized children through online visits with their classmates may be relevant when one-on-one meetings are problematic. The online visits are highly dependent on collaboration between study nurses and teachers and assessing the needs of the hospitalized children. While a high degree of adult engagement and a stable internet connection are pivotal, these online visits can promote much-needed social interaction between children across physical settings.